Prevention of domestic violence against the elderly - O. O. Volodina; T. M. Malynovska (Law and Safety)
Domestic violence is one of the most common forms of human rights violations. Illegal actions against a family member are in most cases accompanied by acts of aggression, humiliation and abuse. Such actions by the abuser lead to a negative physical, mental and social health of the victim or several members of the family. As a rule, women, children and the elderly suffer the most from domestic violence.